1998
DOI: 10.1021/ie9703954
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Anion Sorption by Chitosan Beads:  Equilibrium and Kinetic Studies

Abstract: Chitosan is a well-known biopolymer, whose high nitrogen content confers remarkable ability for the sorption of metal ions from dilute effluents. However, its sorption performance in both equilibrium and kinetic terms is controlled by diffusion processes. Gel bead formation allows an expansion of the polymer network, which improves access to the internal sorption sites and enhances diffusion mechanisms. Molybdate and vanadate recovery using glutaraldehyde cross-linked chitosan beads reaches uptake capacities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
285
1
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(307 citation statements)
references
References 27 publications
14
285
1
7
Order By: Relevance
“…The slight effect of agitation implies that external mass transfer is not the sole rate limiting phase of sorption. However, Findon et al reported that, copper and mercury sorption is not dependent on the agitation speed (Guibal et al, 1998). The results demonstrated that, Chitosan is an effective sorbent of Cr (VI) and the sorption is significantly influenced by parameters such as sorbent concentration, temperature, air pollution concentration, and air velocity.…”
Section: Influence Of Air Velocitymentioning
confidence: 97%
See 1 more Smart Citation
“…The slight effect of agitation implies that external mass transfer is not the sole rate limiting phase of sorption. However, Findon et al reported that, copper and mercury sorption is not dependent on the agitation speed (Guibal et al, 1998). The results demonstrated that, Chitosan is an effective sorbent of Cr (VI) and the sorption is significantly influenced by parameters such as sorbent concentration, temperature, air pollution concentration, and air velocity.…”
Section: Influence Of Air Velocitymentioning
confidence: 97%
“…In the alkaline solution, the beads kept their initial spherical forms and formed chitosan beads ( Fig. 1) (Guibal et al, 1998 andGuibal et al, 1999). The beads were stirred in NaOH solution on the orbital shaker at 250 rpm for 24 h. Then, they were washed three times with distilled water and kept in a 2.5 M NaOH solution at 4 °C.…”
Section: Beads Preparation and Characterizationmentioning
confidence: 99%
“…5 ), C: is the intercept of straight lines, which gives information about the boundary layer thickness [39,40]. On fitting data to the above equation, if the linear correlation value is close to unity, then intraparticle diffusion process is effective onto nanogels.…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…A number of these studies have developed sorption processes including adsorption and ion-exchange mechanisms, precipitation, solvent extraction, conjunction of membranes and polymers using simple materials such as activated carbon or more sophisticated materials such as especially tailored polymers as well as biosorbents, such as fungal or bacterial biomass, and materials of biological origin, including alginate and chitosan [2][3][4][5][6][7][8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%